’Freezing’ as a Manuscript Preservation Method at Sonobudoyo Museum Library - Nurul Setyawati (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Freezing is known as a method that is considered to quickly eradicate active forms of plants and insects so that it can kill insects and their eggs in ancient manuscripts The purpose of this research is to find out more about the causes of ancient manuscript damage and the application of freezing as a form of the ancient manuscript preservation method. The method used in this research is descriptive with an approach. The research method uses a qualitative descriptive approach. While the informants of this study were the Head of the collection, conservation, and preparation section, the Manuscript conservator, the Collection section assistant, and the Manuscript room management officer. Observation, interviews, and documentation are used as data collection methods. The data analysis method, however, makes use of three methods: data reduction, data display, and conclusion. Triangulation of sources to determine the accuracy of the data. The study discovered that insect elements such as silverfish, book lice, and book warm are the main causes of destruction to old texts. As a solution, the freezing method is applied in three stages: pre-freezing, the freezing procedure, and post-freezing. The lack of work safety equipment for officers performing freezing duties was one of the challenges. In addition, the collection was still mostly located on the second floor, making the transfer rather time-consuming.